Belomorsko–Baltiiskii kanal - Lemberg, Alexander (Soviet Union : Sovkino, 1933)
"In order to strengthen the economic connections between the republics of the Soviet Union, Moscow has to be a port of five seas. Therefore the Party, following the directives of Stalin, decided to build a canal that connects the Baltic and the White Seas. " A special insight into the lives of the Soviet forced labour camps.
Duration: 00:33:00
Keywords: Propaganda films